Evaluación técnico financiera del uso de una unidad flush by con varilla hueca para el lavado de arena en el Campo Casabe (2018)
The use of the Flush By Unit, capable of homologizing the work of the Coiled Tubing Unit, in conjunction with HolloRod Pipe better known as Hollow Rod is being used as a task for fluid injection, is technically evaluated, that allows the washing of sand from wells injectors in Campo Casabe. Once the process was defined, the analysis of the fluid mechanics and operating times of the Flush By Unit was carried out, in order to then compare it with the Coiled Tubing Unit, obtaining satisfactory results in the operational variables of the pressure drops and times of operation.